Rectal gel application of Withania somnifera root extract expounds anti-inflammatory and muco-restorative activity in TNBS-induced Inflammatory Bowel Disease - Jagtap Suresh; Sharma Siddhesh; Gilda Suhit; Pawar Pankaj; Paradkar Anant; Mahadik Kakasaheb; Ranjekar Prabhakar; Harsulkar Abhay (BMC, 2011)
Abstract Background Inflammatory Bowel Disease (IBD) is marked with chronic inflammation of intestinal epithelium driven by oxidative stress. Traditional treatments with plant extracts gained renewed interest due to their ability to ameliorate the multi factorial conditions like inflammation. We investigated the beneficial effects of Withania somnifera in Trinitro Benzyl Sulfonic Acid (TNBS) induced experimental IBD through a rectally applicable formulation. Methods The study included (i) preparation of gel formulation from aqueous Withania somnifera root extract (WSRE), (ii) biochemical assays to determine its performance potential, (iii) testing of formulation efficacy in TNBS-induced IBD rat model, and (iv) histo-patholgical studies to assess its healing and muco-regenerative effect in IBD-induced rats. For this purpose, concentration dependant antioxidant activity of the extracts were evaluated using biochemical assays like (a) inhibition of lipid peroxidation, (b) NO scavenging, (c) H2O2 scavenging, and (d) ferric reducing power assay. Results The extract, at 500 μg/ml, the highest concentration tested, showed 95.6% inhibition of lipid peroxidation, 14.8% NO scavenging, 81.79% H2O2 scavenging and a reducing capacity of 0.80. The results were comparable with standard antioxidants, ascorbic acid and curcumin. WSRE treatment positively scored on histopathological parameters like necrosis, edema, neutrophil infiltration. The post treatment intestinal features showed restoration at par with the healthy intestine. In view of these results, gel formulation containing an aqueous extract of W. somnifera, prepared for rectal application was tested for its anti-inflammatory activity in TNBS-induced rat models for IBD. Commercially available anti-inflammatory drug Mesalamine was used as the standard in this assay. Conclusions Dose of the rectal gel applied at 1000 mg of WSRE per kg rat weight showed significant muco-restorative efficacy in the IBD-induced rats, validated by histo-pathological studies.